IMPLEMENTASI METODE MUBASYARAH DALAM PEMBELAJARAN MUHADATSAH - Novi Mutmainah; Lina Marlina (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
Speaking skills are very important skills in learning Arabic, especially in learning Muhadastah because in general speaking skills aim to make students able to communicate verbally properly and correctly. However, in reality the question of the Arabic speaking skills of students in SMP Plus Qurrota Ayun Singaparna is still low. As is known the learning method applied is the direct method. This research was conducted to determine students' Arabic speaking ability through the use of the preacher method in the school. The method used in this research is descriptive analysis method with a qualitative approach. Data collection techniques used were observation, interviews, and documentation studies. The interview results show that the purpose of using the preacher method is so that students are more skilled in speaking Arabic and so students are motivated to speak Arabic. In practice, the teacher prepares vocabulary related to the material then reads the text followed by students repeatedly and the teacher justifies the pronunciation of students who are still wrong. Evaluation of Muhadastah Learning with the Direct Method is carried out by giving individual students assessments in the form of oral and written tests. The obstacle in learning Muhadastah with the method of preaching that is felt by students is that students have difficulty interpreting unknown vocabulary because students have not learned Arabic before. The obstacles felt by the teacher are the teachers find it difficult to deliver the material due to different student backgrounds and many students who do not live in boarding schools.